Peri‐implant soft tissue and marginal bone adaptation on implant with non‐matching healing abutments: micro‐CT analysis. Issue 4 (23rd January 2014) - Finelle, Gary; Papadimitriou, Dimitrios E. V.; Souza, André B.; Katebi, Negin; Gallucci, German O.; Araújo, Mauricio G.
Abstract: Purpose: To assess (i) the outcome of changing the horizontal‐offset dimension on the peri‐implant soft tissues and the crestal bone and (ii) the effect of different healing abutments (flared vs. straight) on the marginal peri‐implant soft tissues and crestal bone. Materials and Methods: Two‐piece dental implants diameters of 3.5 and 4.5 mm were placed at least 1 mm subcrestal in five beagle dogs. Three different investigational groups: (i) 3.5‐mm‐diameter implant with narrow healing abutment (3.5N), (ii) 4.5‐mm‐diameter implant with narrow healing abutment (4.5N), and (iii) 3.5‐mm‐diameter implant with wide healing abutment (3.5W), were assessed. After 4 months of healing, the vertical distance from the marginal crestal bone (MB) to the implant shoulder (IS); the vertical distance from the IS to the first bone‐to‐implant contact; and the horizontal distance of bone ingrowth on the implant platform were measured with a high‐resolution micro‐CT (Xradia MicroXCT‐200 system). Results: Implants with a narrow healing caps showed an interproximal MB located between 0 and 1 mm above the implant shoulder, while the 3.5W group exhibits a mean value −0.50 mm. As all implants in group 3.5N presented a fBIC located at the level of the IS. For the 4.5N group, the mean fBIC‐IS distance was −0.52 mm apically to the IS. For the 3.5WC group, the mean fBIC‐IS distance was −1.42 mm. Horizontal bone apposition was only observed for the 3.5N group and the 4.5N group. Conclusion: The dimension of the horizontal offset would play a minimal role in reducing bone remodeling, whereas the configuration of the transmucosal component would directly influence marginal bone remodeling.